2012
DOI: 10.1002/jmri.23783
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of 1H MR spectroscopy of hip bone marrow at 3 tesla

Abstract: The 3 Tesla (1)H MR spectroscopy of hip bone marrow permitted highly reproducible fat content values in all the five anatomic areas examined. No statistical significant difference existed when comparing fat content values of the right side to those of the left side in the same individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The evaluation of CVl showed a moderate to excellent reproducibility for all lipid resonances in femoral neck and for TL, L13, L16, L23, L16+L09+L13, and L16+L13 resonances in calcaneus. In particular, TL and L13 estimation exhibited an excellent reproducibility ( Table 2) in agreement with previous reliability study performed on the hip (38,39). On the other hand, CVs showed a generally worst reproducibility of data although acceptable and in agreement with the values reported for the estimation of the short range reproducibility of TL in vertebral sites (21).…”
Section: Discussionsupporting
confidence: 90%
“…The evaluation of CVl showed a moderate to excellent reproducibility for all lipid resonances in femoral neck and for TL, L13, L16, L23, L16+L09+L13, and L16+L13 resonances in calcaneus. In particular, TL and L13 estimation exhibited an excellent reproducibility ( Table 2) in agreement with previous reliability study performed on the hip (38,39). On the other hand, CVs showed a generally worst reproducibility of data although acceptable and in agreement with the values reported for the estimation of the short range reproducibility of TL in vertebral sites (21).…”
Section: Discussionsupporting
confidence: 90%
“…MRS‐based vertebral bone marrow fat fraction has been also recently shown to be in good agreement with the bone marrow fat fraction from dual‐energy computed tomography (CT) . Finally, good reproducibility values have been reported for both imaging‐based and MRS‐based bone marrow fat fraction in the spine and the proximal femur …”
Section: Technical Aspects Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…52 Finally, good reproducibility values have been reported for both imagingbased and MRS-based bone marrow fat fraction in the spine 26,53 and the proximal femur. 54,55 Properties of Fat Component In addition to measuring the fat fraction, MRS techniques have been employed to measure bone marrow fatty acid composition, with primary applications in osteoporosis and fracture risk assessment. In a typical MR spectrum, the unsaturation and polyunsaturation levels can be extracted from the olefinic (at 5.4 ppm) and diallylic (at 2.8 ppm) fat peak resonances, respectively.…”
Section: Chemical Shift Encoding-based Water-fatmentioning
confidence: 99%
“…In particular, no participant declared to be treated for osteopenia or osteoporosis. Because it has been recently demonstrated that hip bone marrow spectroscopic values do not differ significantly from right to left side in the same individual , all the volunteers underwent unilateral 1 H MR spectroscopy of the proximal femur that includes acetabulum, femoral head, femoral neck, proximal diaphysis, and greater trochanter.…”
Section: Methodsmentioning
confidence: 99%